Analytic Hierarchy Process: An Application in Green Building Market Research - Attaran, Sharmin; Celik, Bilge Gokhan (International Review of Management and Marketing, 2013)
Sustainability has become a necessity in the building industry. In recent years, as the general public is more informed and aware of sustainability related issues, they are becoming major players in the decision making process regarding their built environment. However, there are still challenges with how sustainability is communicated to occupants and owners of buildings. As the global economic crisis is continuing, the marketing of green buildings needs to be refined to communicate the lifetime benefits of sustainability. One of the ways to develop effective marketing strategies, is to understand what the occupants value the most among many aspects of green buildings thus develop focused marketing solutions. Authors present a conceptual methodology using Analytic Hierarchy Process toward identifying consumer ranking and weights of a major green building rating system’s categories. Authors use sample non-representative data to illustrate the proposed methodology, while sharing preliminary qualitative data from the research in progress. Keywords: LEED; Sustainable Buildings; Sustainability Marketing; Occupant Value; Criteria Weightings; AHP JEL Classifications: C44; D81; M31